2003
DOI: 10.1029/2002jd002436
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the heterogeneous hydrolysis of N2O5 on chemistry and nitrate aerosol formation in the lower troposphere under photosmog conditions

Abstract: [1] The impact of the heterogeneous hydrolysis of N 2 O 5 on tropospheric gas phase and particle phase chemistry was investigated by performing model simulations with two comprehensive model systems and taking into account recent findings on the heterogeneous reaction probability of N 2 O 5 . Hereby, we focused on photosmog conditions in the lower troposphere. Chemistry box model runs were carried out neglecting transport and deposition processes. The heterogeneous hydrolysis of N 2 O 5 leads to a decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
242
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(254 citation statements)
references
References 44 publications
8
242
1
2
Order By: Relevance
“…The lower ClNO 2 /N 2 O 5 ratios during P2 compared with P1 can be explained by the "nitrate effect", which suppressed N 2 O 5 uptake (Mentel and Wahner, 1999) as P2 showed much higher nitrate concentrations than P1 (4.2 vs. 1.4 µg m −3 ). Note that the ClNO 2 /N 2 O 5 ratios were also characterized by a dependence on Org / SO 4 ratios in our campaign, similar to other studies (Evans and Jacob, 2005;Riemer et al, 2009). …”
Section: Relationship Between N 2 O 5 and Clnosupporting
confidence: 78%
See 1 more Smart Citation
“…The lower ClNO 2 /N 2 O 5 ratios during P2 compared with P1 can be explained by the "nitrate effect", which suppressed N 2 O 5 uptake (Mentel and Wahner, 1999) as P2 showed much higher nitrate concentrations than P1 (4.2 vs. 1.4 µg m −3 ). Note that the ClNO 2 /N 2 O 5 ratios were also characterized by a dependence on Org / SO 4 ratios in our campaign, similar to other studies (Evans and Jacob, 2005;Riemer et al, 2009). …”
Section: Relationship Between N 2 O 5 and Clnosupporting
confidence: 78%
“…Previous laboratory studies have shown a large variability of γ N 2 O 5 (0.0002-0.3) depending on the physical characteristics of the substrates (e.g., aerosol surfaces, water droplets, and ice and crystal surfaces), environmental conditions (e.g., acidity, relative humidity, and temperature), and chemical composition of aerosol particles (e.g., nitrate, sulfate, black carbon, and organic coating; Sander et al, 2006;Chang et al, 2011;Anttila et al, 2006;Cosman et al, 2008;Thornton and Abbatt, 2005;McNeill et al, 2006). To reveal the effects of each factor on N 2 O 5 /ClNO 2 chemistry, several parameterizations of γ N 2 O 5 and ø have been proposed during the last decade (Riemer et al, 2003;Evans and Jacob, 2005;Anttila et al, 2006;Davis et al, 2008;Riemer et al, 2009;Griffiths et al, 2009). For example, Bertram and Thornton (2009) constructed a parameterization of γ N 2 O 5 as a function of aerosol liquid water, nitrate, and chloride content based on the measurements of laboratory-generated internally mixed chloride-nitrate particles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the formation of secondary particles from gaseous precursors and particle dynamics has been added to the physical and chemical processes handled in AQMs (Binkowski and Shankar, 1995;Ackermann et al, 1998;Binkowski, 1999;Schell et al, 2002, Riemer et al, 2003.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The hydrolysis of N 2 O 5 on wet aerosol surfaces is an important pathway to convert NO x into HNO 3 (Dentener and Crutzen, 1993;Riemer et al, 2003;Schaap et al, 2003a, b):…”
Section: No Xmentioning
confidence: 99%